1987
DOI: 10.1029/ja092ia13p14987
|View full text |Cite
|
Sign up to set email alerts
|

The atmosphere of Uranus: Results of radio occultation measurements with Voyager 2

Abstract: During Voyager 2's occultation by Uranus the radio link from the spacecraft probed the atmosphere of the planet at latitudes ranging from 2 ø to 7 ø south. The measurements, which were conducted at two coherently related wavelengths, namely, 13 cm (S band) and 3.6 cm (X band), did not show any clear signs of microwave absorption. However, the Doppler frequency perturbations observed on the radio link have provided new data on the equatorial radius and atmosphere of the planet. From integral inversion of the Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
276
3
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(302 citation statements)
references
References 49 publications
20
276
3
3
Order By: Relevance
“…It has been found on the surface of several icy bodies in the Solar System Owen et al 1993;Brown et al 2005;Licandro et al 2006), such as the icy clouds of Jovian planets (Lindal et al 1987;Smith et al 1989), and of Saturn's moon Titan (McKay et al 1997;Griffith et al 1998;Brown et al 2002), and on the surface of Pluto and of Neptune's satellite Triton (Lanzerotti et al 1987). Methane ices have also been found throughout the interstellar medium (Lacy et al 1991;Boogert et al 1996;Gibb et al 2004;Öberg et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…It has been found on the surface of several icy bodies in the Solar System Owen et al 1993;Brown et al 2005;Licandro et al 2006), such as the icy clouds of Jovian planets (Lindal et al 1987;Smith et al 1989), and of Saturn's moon Titan (McKay et al 1997;Griffith et al 1998;Brown et al 2002), and on the surface of Pluto and of Neptune's satellite Triton (Lanzerotti et al 1987). Methane ices have also been found throughout the interstellar medium (Lacy et al 1991;Boogert et al 1996;Gibb et al 2004;Öberg et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…The radio-optic method was used for processing soundings of planetary atmospheres [Lindal et al, 1987], and recently its application to GPS radio occultation data was suggested [Pavelyev, 1998]. The method is based on the analysis of the local spatial spectra of the measured complex wave field.…”
Section: Radiosoptic Methodsmentioning
confidence: 99%
“…It has been successfully used for many bodies in the solar system, including Jupiter and its satellites (Eshleman, 1975;Hinson et al, 1997), Saturn (Lindal et al, 1985), Uranus (Lindal et al, 1987), Neptune and Triton (Lindal, 1992), Mars (Cahoy et al, 2006), and Venus (Jenkins et al, 1994;Hinson and Jenkins, 1995). Prior to Cassini, the Voyager 1 spacecraft was occulted by Titan in 1979, early in Titan's northern spring (Lindal et al, 1983).…”
Section: Introductionmentioning
confidence: 99%